Análisis comparativo de procedimientos de identificación de dismorfismo eritroide en pacientes con hematuria y en individuos sanos - Guerra de Muñoz, Martha; Alvarez Zuluaga, Martha Leonor (Universidad y Salud, 2005)
Diagnosis of microscopic renal glomerular haematuria is one of the major problems in nephrology, and several studies have been conduce on urine sediments to identify erythrocytes of glomerular origin. Birch and Fairley were the firts investigators who have reported that erythrocytes leaking from renal glomeruli were dysmorphic, in contrast to normal erythrocytes of non-glomerular origin. This finding proved to be of value in identifying patients with glomerular bleeding in some studies. However, other studies failed to demonstrate either a high sensitivity or specifity of urinary dysmorphic erythrocytes as an indicator for glomerular bleeding. In recent years, G1 cells or urinary erythrocytes with doughnut-like shape, target configuration and membranous protrusions or blebs have been reported by Tomita et al. and by other invetigators as a reliable marker for glomerular haematuria.